2018
DOI: 10.21873/cgp.20091
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Receptor Antagonists' Action on HDAC Expression Eliminating the Negative Effects of Leptin in Ovarian Cancer

Abstract: SHLA and Lan2 eliminate the negative effects of leptin on HDAC expression in a cell-type-dependent manner. This is the first report testing leptin receptor blockers as HDAC inhibitors in ovarian cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Another study showed that ob/ob and db/db mice exhibited a reduction in sirtuin 1 (SIRT1) expression, a histone deacetylase, in comparison to C57BL/6J mice [58]. Furthermore, a great body of research is now focused on obesity-related carcinogenesis, which occurs due to, among others, hyperleptinemia [59]. For instance, the expression of SIRT1 was upregulated via leptin-induced, nuclear factor, erythroid 2 Like 2 (Nrf2)-dependent signaling in colon cancer [58].…”
Section: Leptin-induced Epigenetic Modifications In Metabolic Disomentioning
confidence: 99%
“…Another study showed that ob/ob and db/db mice exhibited a reduction in sirtuin 1 (SIRT1) expression, a histone deacetylase, in comparison to C57BL/6J mice [58]. Furthermore, a great body of research is now focused on obesity-related carcinogenesis, which occurs due to, among others, hyperleptinemia [59]. For instance, the expression of SIRT1 was upregulated via leptin-induced, nuclear factor, erythroid 2 Like 2 (Nrf2)-dependent signaling in colon cancer [58].…”
Section: Leptin-induced Epigenetic Modifications In Metabolic Disomentioning
confidence: 99%
“…Therefore, the American authors recently demonstrated that although patients developing postoperative complications had a lower rate of survival at one year follow up (the one year overall survival being of 77.2% for patients which reported postoperative complications, and 89% for patients with uneventful postoperative evolution) and despite the association between extended resections and postoperative complications; the overall survival of patients submitted to extended visceral resections was significantly improved at one year (18). In this respect, other factors influencing the poorer outcomes of patients developing postoperative complications should be investigated (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a study on human colon cancer cells, leptin was found to up-regulate the expression of histone deacetylase enzyme sirtuin 1 (SIRT1) ( Song et al, 2018 ) . In another study in ovarian cancer, it was reported that leptin modulated HDACs gene expression, in which class I and II HDACs were increased in OVCAR-3 cells, while class II HDAC expression was increased in folliculoma cells ( Fiedor et al, 2018 ). Importantly, animals with dysregulated leptin signalling, the diabetic mouse (db) and obese mouse (ob), showed lower expression of SIRT1 in colon cells, suggesting its involvement in leptin-induced pathogenesis of colon carcinogenesis ( Song et al, 2018 ).…”
Section: Leptin and Methylation Changesmentioning
confidence: 99%